Analysis of the Public Satisfaction Levels on the Issuance Rate Policy of Drugs Test Result Certificate : (Evaluation of the Government Regulation No.19 of 2020) - Sri Annisya; Palupi Lindiasari Samputra (PT Mattawang Mediatama Solution, 2023)
This study aims to evaluate the public satisfaction levels of users related to the Drug Test Result Certificate (SKHPN) issuance services related to the rates set by the Government based on Government Regulation No.19 of 2020 concerning Types and Rates of Non-Tax State Revenues (PNBP) that apply to the National Narcotics Agency (BNN). The research method used in this study is quantitative research with survey methods. The research was conducted at the National Narcotics Agency of South Sumatra Province. The study subject employed people who use SKHPN publishing services in the BNN work area of South Sumatra Province. Data collection instruments used questionnaires through Google Forms, distributed via the WhatsApp application. The research sample was 137 respondents selected by Purposive Sampling techniques. The data analysis method used a Community Satisfaction Survey (SKM) based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Indonesia Republic Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Delivery Units. The results showed that the SKHPN rate policy was included in the good category with an average SKM value of 3,45 (B). However, the cost indicator was included in the bad category with an average SKM value of 1,957 (D).